(untitled) (Fiep Bulletin - online, 2015)
A Project of statutes for an international literature competition on the Theory of Physical Education was approved of at the FIEP’s General Assembly on the 20th July 1939 in Stockholm and another similar project of rules was also approved of at the General Assembly of the same Organization held during the World Congress of physical and Sportive Education held in Madrid from 13th to 18th September 1966.